Is Knee Arthroscopy Beneficial in Treating Traumatic Meniscal Tears on Patients Older Than 60 Years? - Li, Ke; Cavaignac, Etienne; Chen, Hong; Xu, Wei; Chen, Cheng; Huang, Wei (The Journal of Knee Surgery, 2018)
Knee arthroscopic surgery is usually performed on young or middle-aged patients with meniscal tears. However, we have noted an amount of active elderly patients who suffered from traumatic meniscal tear without significant degenerative changes. Outcome data were prospectively collected and retrospectively reviewed in patients older than 60 years who underwent partial arthroscopic meniscectomy between April 2008 and July 2013. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, Kellgren–Lawrence (K–L) grade, Knee Society Score (KSS), and pain scores were collected, and conversion to total knee arthroplasty (TKA) was recorded. Subgroups comparing the clinical outcome of different level of K–L grade and Outerbridge's score were conducted. At an average of 31 months of follow-up (standard deviation [SD]: 8.9; range, 24–63 months) for 96 patients with a mean age of 65.8 years (SD: 5.7; range, 60–83 years), 12 patients underwent conversion to TKA at an average of 2.1 years. Patients with a clear traumatic history of the knee have better improvement in visual analog scale (p < 0.001), KSS functional score (p = 0.005), and WOMAC score (p < 0.001), patients with K–L grade greater than III were 3.1 times more likely to undergo conversion to TKA than patients with K–L grade less than III. The findings indicate that patients older than 60 years with mild osteoarthritis and clear traumatic history of the meniscus are a good indication for arthroscopic partial meniscectomy. The level of evidence is level IV (a retrospective case series).
Keywords: knee arthroscopy; osteoarthritis; traumatic meniscal tears; elderly patients